2007
DOI: 10.1080/10473289.2007.10465337
|View full text |Cite
|
Sign up to set email alerts
|

Indoor- and Outdoor-Derived Contaminants in Urban and Rural Homes in Ottawa, Ontario, Canada

Abstract: Indoor and outdoor air contaminants have largely been treated separately in studies of their respective effects on respiratory and nonrespiratory health. In this paper, we report the results of a comprehensive study of key contaminants in 10 urban and 10 rural homes in Ottawa, Ontario, Canada. The analyses included house dust mite and cat allergens along with the fungal inflammatory polysaccharide ␤1,3-D-glucan in settled dust and fine particulate matter, coarse particulate matter, ergosterol, glucan, and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
8
28
0
Order By: Relevance
“…This finding agrees with the results by Miller et al (2007). Considerable differences, however, were found in average indoor room concentrations between Homes A to C; particularly large differences were seen in beta-glucan concentrations measured in the kitchens.…”
Section: (1?3)-b-d-glucansupporting
confidence: 92%
See 1 more Smart Citation
“…This finding agrees with the results by Miller et al (2007). Considerable differences, however, were found in average indoor room concentrations between Homes A to C; particularly large differences were seen in beta-glucan concentrations measured in the kitchens.…”
Section: (1?3)-b-d-glucansupporting
confidence: 92%
“…The investigators concluded that the levels of beta-glucans are higher during the warm seasons, which may be attributed to the seasonal variation of pollen and fungal spores. Miller et al (2007), who measured airborne beta-glucan, ergosterol, and endotoxin in living rooms and bedrooms in 20 Canadian homes using long-term air sampling, reported no difference between the two room types in any of the measured biocontaminants. Chew et al (2001) analyzed beta-glucan in dust samples collected in 23 Dutch homes over a period of a year and found similar variation of its levels within and between homes.…”
Section: Introductionmentioning
confidence: 97%
“…(1→3)-β-D-glucan, glucose polymers with variable molecular weights and degrees of branching (i.e., triple helix, single helix, or random coil structures), are found in most fungi, plants and certain bacteria, and can be used to monitor levels of fungi. Indoor airborne endotoxin, (1→3)-β-D-glucan, and protein concentrations have been reported in the literature as a part of non-industrial indoor environmental studies (Park et al 2000(Park et al , 2001Reynolds et al 2001;Rylander and Beijer 2003;Foarde and Berry 2004;Sohy et al 2005;Chew et al 2006;Lee et al 2006;Solomon et al 2006;Miller et al 2007), epidemiological studies (Rylander et al 1992;Rylander 1997;Rylander et al 1998; Thorn and Rylander 1998;Wan and Li 1999) and toxicological studies (Monn and Becker 1999;Rylander and Lin 2000;Long et al 2001;Soukup and Becker 2001;Beijer et al 2002).…”
Section: Introductionmentioning
confidence: 94%
“…This appears to be the first report on LAL-analyzed (1-3)--D-glucan concentration in a large number of dust samples. The LAL-analyzed dust (1-3)--D-glucan levels measured in this study were lower than those measured in Canadian homes (n=28) of asthmatic children (GM=172 g/g and GM=160 g/m 2 ) [45] and homes perceived as having satisfactory indoor quality (n=20) (median=230 g/m 2 ) [46]. These differences may be due to different geography and/or heating [16] (in colder climate) in the Canadian homes.…”
Section: Discussionmentioning
confidence: 61%
“…The EIA assay is not commercially available, and is not generally performed in most clinical laboratories. In addition, less data are available on the utility of LAL and EIA assays in the analysis of fungal (1-3)--Dglucan concentration in environmental samples [4,5,45,46]. Thus, the current study is the first one to directly compare the specificity, sensitivity, and accuracy of LAL versus EIA assays in detecting fungal (1-3)--D-glucans.…”
Section: Discussionmentioning
confidence: 99%